The Analysis of Complex Networks with Dynamic Graph Visualization - S. N. Pupyrev; A. V. Tikhonov (Моделирование и анализ информационных систем)
The work describes a technique for dynamic graph visualization that helps us to analyze complex networks. Our method builds layouts for a sequence of graphs, while preserving the mental map. We show how to modify force-directed algorithms for the dynamic graphs. The proposed method is applied for visualization of several social networks. The experiments demonstrate the effectiveness of dynamic graph drawing for analyzing real-world data and the evolution of social relationships changing over time.